Pregnant Woman Hemoglobin Levels and Baby Birth Weight - Mareza Yolanda Umar; Psiari Kusuma Wardani (Universitas Aisyah Pringsewu, 2022)
Neonatal mortality rate is one indicator to ensure public health status. One of the main factors that influence perinatal and neonatal mortality is low birth weight (LBW). Low birth weight babies (LBW) and anemia in newborns are caused by pregnant women who are iron deficient or anemic. This research aims to determine the hemoglobin levels of pregnant women with infant birth weight in the working area of the UPT Puskesmas Karang Anyar, Jati Agung Regency. South Lampung in 2021.This type of research is quantitative, with an analytic design and a case control approach. This research was carried out in June with the population used in the form of maternal data in 2021 in the working area of the Karang Anyar Health Center UPT, while the number was 70. The sampling technique was a purposive sampling system. This research uses univariate and bivariate analysis with chi square test.The results of the analysis showed that there was a relationship between hemoglobin levels of pregnant women and birth weight in the working area of the Karang Anyar Public Health Center, Jati Agung District, South Lampung Regency, the p-value was 0.000 (0.05) and the odds ratio was 9.264 (28.462 – 3.015). It is hoped that the results of this study can increase the mother's knowledge about the dangers of low hemoglobin and the mother can further increase the ANC and check hemoglobin levels so that it does not pose a risk of low birth weight or other complications and can prevent anemia in pregnant womenAbstrack: Angka kematian neonatal jadi Salah satu penunjuk guna memastikan derajat kesehatan masyarakat. Salah satu factor utama yang pengaruhi kematian perinatal serta neonatal ialah Berat Bayi Lahir Rendah (BBLR). berat bayi lahir rendah (BBLR) serta anemia pada bayi yang baru saja dilahirkan dikarenakan oleh ibu hamil yang Kekurangan zat besi ataupun anemia, Riset ini bertujuan mengetahui kadar hemoglobin ibu hamil dengan berat badan lahir bayi di daerah kerja UPT Puskesmas Karang Anyar Kecamatan Jati Agung Kabupaten Lampung Selatan tahun 2021. Jenis penelitian adalah kuantitatif, dengan desain analitik dan pendekatan case control. Penelitian ini telah dilaksanakan pada bulan juni dengan populasi yang digunakan berupa data ibu bersalin tahun 2021 di wilayah kerja UPT Puskesmas Karang Anyar, adapun jumlah nya yaitu 70. Teknik pengambilan sampel adalah dengan system purposive sampling. Penelitian ini memakai analisis univariat serta bivariat dengan uji chi square.Hasil analisis menunjukan ada hubungan kadar hemoglobin ibu hamil dengan berat badan lahir di wilayah kerja UPT Puskesmas Karang Anyar Kecamatan Jati Agung Kabupaten Lampung Selatan, didapatkan p-value 0.000 (0.05) dan odds ratio sebesar 9.264. Diharapkan hasil penelitian ini dapat menambah pengetahuan ibu tentang bahayanya hemoglobin yang rendah dan ibu dapat lebih meningkatkan ANC dan pemeriksaan kadar hemoglobin agar tidak menimbulkan resiko BBLR ataupun komplikasi lain serta dapat mencegah anemia pada ibu hamil.